Evaluasi Program Perpustakaan Keliling di Kantor Perpustakaan Arsip dan Dokumentasi Kabupaten Dharmasraya - Ervan, Uly Fitri; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2013)
This paper is aimed to describe: an evaluation program of mobile library in library archieves and documentary office in Dhamasraya regency and several factors that disturb the evaluation program of mobile library in library archieves and documentary office in Dhamasraya regency. Method used in this paper is qualitative method. The data used is collected through direct observation, interview and literature study. The data is analyzed by using descriptive method. Based on the study, it can be concluded that (1) the evaluation program of mobile library in libraryÂ  archieves and documentary office in Dhamasraya region is held in several ways (a) the human resources planning is not very good. This activity need to be evaluated, because it lacks of skillfull librarian so the goverment need to select and choose a good staff. In order to make the program work good, (b) the organization in mobile library in Dhamasraya region is not very good, (c) the explanation in mobile libraray in Dhamasraya is quite good, where the librarians take a good responsibility to their works, (d) the budget of mobile library in Dhamasraya need to be increased in order to enhance the program, (2) several factors that disturb the evaluation program in mobile library in library, archieves and documentary office in Dhamasraya are lack of budget, lack of human resource, and there is no regulation about evaluation. Keywords: evaluation collection; mobile library